Ranibizumab for branch retinal vein occlusion associated macular edema study (RABAMES): six-month results of a prospective randomized clinical trial - Pielen, Amelie; Mirshahi, Alireza (Acta ophthalmologica, 2015)
Purpose To compare standard-of-care grid laser photocoagulation versus intravitreal ranibizumab (IVR) versus a combination of both in the treatment of chronic (>3 months) macular oedema secondary to branch retinal vein occlusion. Methods Prospective, randomized, multicentre clinical trial. Thirty patients with a best-corrected visual acuity (BCVA) between 20/320 and 20/40 were randomized 1:1:1 to receive grid laser or three monthly injections of 0.5 mg IVR or both followed by 3 months of observation. Results Mean change from baseline BCVA at month 6 was +2 letters [laser; 0.04 logMAR, 95% confidence interval (-0.17; 0.25)], +17 letters [IVR; 0.34 (0.19; 0.5)] and +6 letters [combination; 0.12 (0.01; 0.24)] (IVR versus laser p = 0.02 and IVR versus combination p = 0.02). At month 3, mean improvement in central retinal thickness (CRT) was 90.6 μm (laser) (-18.65; 199.8), 379.5 μm (IVR) (204.2; -554.8), and 248 μm (167.2; -328.8) (combination) (IVR versus laser p = 0.005, laser versus combination p = 0.02). During the observation period, CRT improved in laser [37.6 μm (-66.82; 142.0)], but deteriorated in IVR [-142.4 μm (-247.6; -37.16)] and combination [-171.7 μm (-250.4; -92.96)] (laser versus IVR p = 0.01, laser versus combination p = 0.002) indicating recurrent oedema. Less laser retreatments (at 8 weeks) were required in combination group (2/10) than grid group (7/10). Conclusion Six-month results suggest that ranibizumab may be superior to grid laser in improving visual acuity. Grid combined with IVR neither enhanced functional and morphological improvement of IVR nor did it prevent or prolong recurrence of oedema. In IVR groups, CRT increased slowly after stopping injections, whereas improvement in visual acuity was sustained, indicating that morphological changes occur prior to functional impairment.
Gesehen am 22.11.2018
First published: 08 July 2014